(3JaSjQ GdchGTi GdeNJUQs - (3CMeO Hf jhSa Hf GdMSf Hf QGaY GHf GdMSjf Hf ShjOGf GdTjHGfqj GdehUdj, ehab GdOjf CHh GdYHGS GdchGTj , J (B680 (3g`s ((3YHO GdbGgQ Hf eMehO Hf CHj HcQ GdScGcjfi s)
(3ChdgG (B:s
(3jHOC HJaSjQ ShQI GdaGJMI s
(3BNQgG (B:s
(3jfJgi HBNQ ShQI GdGSQGA s
(3GdejcQhajde JGdas
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B274 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B209s
Keywords: (3GdJaSjQ hYdhe GdbQBfs